PASANG SURUT TRANSPORTASI KERETA API BATUBARA SAWAHLUNTO-PADANG PANJANG-PADANG TAHUN 1990-2002 - Safitri, Yennita; Husnita, Liza; Kharles, Kharles (Pendidikan Sejarah, 2013)
ABSTRACT The train is one form of land transportation facilities that have special characteristics and advantages , including train could transport people and goods en masse . Allocation of coal mined is suitable Ombilin done by means of rail transport over time, in West Sumatra , more specifically on the track Long Sawahlunto - Padang - Padang . With the goal is ( 1 ) the development of rail freight transport coal Sawahlunto years 1990-2002 , ( 2 ) determine the factors that influence the development path Sawahlunto - Padang - Padang Panjang as a means of mass transit . Based on the above research objective methods used in this study is the historical method . Producer encountered during this study were : ( 1 ) heuristic , ( 2 ) Criticism Sources , ( 3 ) Interpretation , ( 4 ) Historiography . Coal freight rail transportation Sawahlunto - Padang - Padang Panjang tide and tide had dropped , where the railway used by many people as a conveyance of choice for the community . 1990 as the year that experienced high tide for rail because at that moment in coal exports have increased , are ups and downs in 1996 where the use of rail transport is no longer widely used by the public, especially PT . BA UPO , and 2002 was the year in which the train is experiencing changer function as a tourism train . Keywords : Tides of Railway TransportÂ